Introduction to the Gamelan Semar Pagulingan in the Batur Traditional Village | Pengenalan Gamelan Semar Pagulingan Di Desa Adat Batur - Radha, Aghastya (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Batur Village, Kintamani District, Bangli Regency, is well-known for Gong Gede and Baris Dance arts. Still, in the field of arts, especially musical art in middle-class gamelan, one of which is the Semar Pagulingan gamelan, it is essential. This is because the people of Batur Village are more focused on Old Gamelan, such as Gong Gede. At the same time, the middle-class gamelan (Semar Pagulingan) is not yet well known for its characteristics, functions and techniques; is like the gong gede gamelan. Therefore, Batur Village submitted a letter requesting that there be KKN students in Batur Village to provide a clear path to the Semar Pagulingan gamelan. In Batur Village, no pioneers know about the Semar Pagulingan gamelan. The Semar Pagulingan gamelan has a patet system, which is unlike Gong Kebyar or Gong Gede. Our solution at this Thematic Real Work Lecture (KKNT) is training in the Semar Pagulingan gamelan on tempek undagi, which the author will initiate. In this way, students can provide reinforcement, training and knowledge.